Measuring Cardiopulmonary Complications of Carfilzomib Treatment and Associated Risk Factors Using the SEER-Medicare Database - Fakhri, Bita (Cancer, 2019)
BACKGROUND. Carfilzomib improves survival in patients with relapsed myeloma. Given the strict eligibility criteria in the clinical trials, the actual frequency of cardiac (CAEs) and pulmonary adverse events (PAEs) and risk factors associated with these AEs in the general population needs to be established. METHODS. We extracted myeloma cases in the SEER-Medicare linked database from 2000-2013 and corresponding claims through 2014. We then identified patients who received carfilzomib during their disease course. Subsequently, we used the International Classification of Disease, ninth revision (ICD-9) to identify all the codes for CAEs, PAEs and respiratory infections associated with carfilzomib use. Pre-existing diagnoses corresponding to the CAEs and PAEs of interest were excluded to distinguish toxicity from comorbidity. Multivariate Cox regression was performed to determine the variables independently associated with developing CAEs and PAEs. RESULTS. Among 635 patients analyzed, the median age was 72 (range 36-94); 55% of the patients were male and 79% Caucasian. The median duration of carfilzomib treatment was 58 days (range 1-716). Overall, 66% had codes for either CAEs or PAEs. In terms of CAEs, 22% developed hypertension, 15% peripheral edema and 14% heart failure. In terms of PAEs, 28% developed dyspnea, 15% cough, and 15% pneumonia. Only COPD was independently associated with developing CAEs. Patients with pre-existing COPD had a 40% increase in hazard for developing CAEs (aHR 1.40, 95% CI 1.03-1.90). CONCLUSIONS. In older adults with myeloma receiving carfilzomib, new cardiac and pulmonary diagnoses were common. Patients with pre-existing COPD were at increased risk for developing CAEs.